Hepatoprotective Activity of Curcuma mangga Extract on Paracetamol-Induced Male Mice - Marianne; Yuandani; Mardaliza, Silvia (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
This study was carried out to investigate the protective effect of ethanol extract of Curcuma mangga rhizomes on paracetamol-induced hepatotoxicity. High dose of paracetamol (1.35g/kg bw) was used to induce hepatic necrosis of mice liver. The male mice received ethanol extract of C. mangga rhizomes (100, 200 and 400 mg/kg BW) for 7 days. The hepatoprotective actvity of extract was compared to normal, positive (curcuma) and negative control. The liver function was evaluated by measuring the biochemistry parameters which include alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In addition, histophatological study on hepatic tissue section was also carried out. The C. mangga extract displayed hepatoprotective effect except at dose of 100 mg/kg bw. The increasing of serum levels of AST and ALT were inhibited after treatment with ethanol extract at doses of 200 and 400 mg/kb bw which was comparable with normal and curcuma as postive control (p>0.05). In addition, histological assessment of hepatic tissue demonstrated no liver damage, specially at dose of 400 mg/kb BW. The result indicate that ethanol extract of C. mangga rhizomes has hepatoprotective effect, especially at doses of 200 and 400 mg/kg bw . Keywords: C. mangga, rhizomes, biochemistry parameters, histopathology